DAKWAH DALAM KONTEKS PLURALITAS BUDAYA LOKAL - Muridan, Muridan (KOMUNIKA: Jurnal Dakwah dan Komunikasi, 2007)
Islam is religion which is spread out with da ’wa activities. Without that, it would not be as developed as nowadays. In spreading out Islamic teaching to the mad’u, wisdom is really needed. One way to actualize it is by considering the social conditions of the mad’u. In connection with the plurality of local and national cultures, there are several approaches that can be applied in Islamic preaching. In this application, the cultures of the mad’u should be an important consideration. Among the approaches are bayani, burhani and irfani (textual, contextual, and sufistic esoteric approaches). If these approaches do not work well, realistic approach may be applied. This approach tries to meet the substance of Islamic doctrine and the social condition of the mad’u. In this case, Islam as given religion should show its self realistically in the cultural plurality and it is influenced by its history and social conditions of its mad’u. It is not paradox. As a result, in realistic approach, Islam should be able to show its accomodation to the mad’u and be critical to the development of the society.